2019
DOI: 10.1002/ange.201901228
|View full text |Cite|
|
Sign up to set email alerts
|

Unusual Length Dependence of the Conductance in Cumulene Molecular Wires

Abstract: Cumulenes are sometimes described as “metallic” because an infinitely long cumulene would have the band structure of a metal. Herein, we report the single‐molecule conductance of a series of cumulenes and cumulene analogues, where the number of consecutive C=C bonds in the core is n=1, 2, 3, and 5. The [n]cumulenes with n=3 and 5 have almost the same conductance, and they are both more conductive than the alkene (n=1). This is remarkable because molecular conductance normally falls exponentially with length. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…Although less stable than polyynes, [9]cumulenes have been characterized, and functionalized [3]-and [5]cumulenes have been measured in single-molecule junction experiments. 13,[19][20] The single-molecule conductance of odd-n cumulenes is expected to be higher than that of equivalent polyynes due to the smaller bond-length alternation, which narrows the HOMO-LUMO gap. 55 ELECTRONIC STRUCTURE.…”
Section: Odd-n Cumulenic Carbon Wiresmentioning
confidence: 99%
See 2 more Smart Citations
“…Although less stable than polyynes, [9]cumulenes have been characterized, and functionalized [3]-and [5]cumulenes have been measured in single-molecule junction experiments. 13,[19][20] The single-molecule conductance of odd-n cumulenes is expected to be higher than that of equivalent polyynes due to the smaller bond-length alternation, which narrows the HOMO-LUMO gap. 55 ELECTRONIC STRUCTURE.…”
Section: Odd-n Cumulenic Carbon Wiresmentioning
confidence: 99%
“…Owing to the orientation of the end-groups, there is not much electronic communication through the p-systems of the molecule; the single-molecule conductance of a functionalized [2]cumulene (allene) was recently measured to be almost two orders of magnitude lower than that of the equivalent [3]cumulene. 19 However, we recently demonstrated that the electronic transmission through even-n cumulenes can be almost as high as that of the equivalent odd-n systems by splitting the helical frontier molecular orbitals using pyramidalized p-donor substituents. Strategies for manipulating the helical electronic structure of cumulenes using substituents is described in detail elsewhere.…”
Section: Even-n Cumulenic Carbon Wiresmentioning
confidence: 99%
See 1 more Smart Citation
“…Although less stable than polyynes, [9]cumulenes have been characterized, and functionalized [3]-and [5]cumulenes have been measured in single-molecule junction experiments. 13,[19][20] The single-molecule conductance of odd-n cumulenes is expected to be higher than that of equivalent polyynes due to the smaller bond-length alternation, which narrows the HOMO-LUMO gap. 55 ELECTRONIC STRUCTURE.…”
Section: Odd-n Cumulenic Carbon Wiresmentioning
confidence: 99%
“…The foundational experiments of Nongjian Tao 1 and subsequent work exploring charge transport through single molecules connected to two metallic electrodes 2 4 have led to the design of molecular-scale components such as switches, 4 6 rectifiers, 7 and highly conjugated molecular wires. 8 A more recent goal of this research is the design of thermoelectric materials 9 or devices 10 based on single molecules or self-assembled monolayers, 11 which can convert heat into electricity and contribute to the global challenge of green energy harvesting. Such organic materials and devices are potentially lightweight, flexible, environmentally friendly and cost-effective.…”
mentioning
confidence: 99%